KARAKTERISTIK USAHA KECIL DI INDONESIA Perencanaan Pemasaran Usaha Kecil Rumahan - Nugroho, Sidiq Permono (Universitas Muhammadiyah Surakarta, 2010)
This paper describes briefly the rules which is closely related to the problems and obstacles in starting a home-based small businesses and explanations based on theories from several sources as a reference in running a small business home